Green Synthesis of Silver Nanoparticles Using Hypericum perforatum L. Aqueous Extract with the Evaluation of Its Antibacterial Activity against Clinical and Food Pathogens - Abdalrahim Alahmad; Wael A. Al-Zereini; Tahani J. Hijazin; Osama Y. Al-Madanat; Ibrahim Alghoraibi; Omar Al-Qaralleh; Samer Al-Qaraleh; Armin Feldhoff; Johanna-Gabriela Walter; Thomas Scheper (MDPI AG, 2022)
The rapid development of nanotechnology and its applications in medicine has provided the perfect solution against a wide range of different microbes, especially antibiotic-resistant ones. In this study, a one-step approach was used in preparing silver nanoparticles (AgNPs) by mixing silver nitrate with hot Hypericum perforatum (St. John's wort) aqueous extract under high stirring to prevent agglomeration. The formation of silver nanoparticles was monitored by continuous measurement of the surface plasma resonance spectra (UV-VIS). The effect of St. John's wort aqueous extract on the formation of silver nanoparticles was evaluated and fully characterized by using different physicochemical techniques. The obtained silver nanoparticles were spherical, monodisperse, face-centered cubic (fcc) crystal structures, and the size ranges between 20 to 40 nm. They were covered with a capping layer of organic compounds considered as a nano dimension protective layer that prevents agglomeration and sedimentation. AgNPs revealed antibacterial activity against both tested Gram-positive and Gram-negative bacterial strains causing the formation of 13-32 mm inhibition zones with MIC 6.25-12.5 µg/mL; Escherichia coli strains were resistant to tested AgNPs. The specific growth rate of S. aureus was significantly reduced due to tested AgNPs at concentrations ≥½ MIC. AgNPs did not affect wound migration in fibroblast cell lines compared to control. Our results highlighted the potential use of AgNPs capped with plant extracts in the pharmaceutical and food industries to control bacterial pathogens' growth; however, further studies are required to confirm their wound healing capability and their health impact must be critically evaluated.